Faktor yang mempengaruhi kinerja pembiayaan bagi hasil Bank Syariah di Indonesia - Okviana, Dian (CV. Kurnia Grup, 2023)
The purpose of this study is to analyze the effect of Good Corporate Governance on the Performance of Sharia Bank Profit Sharing in Indonesia, to analyze the effect of Investment Account Holders on the Performance of Sharia Bank Profit Sharing in Indonesia, to analyze the effect of Bank Capital on the Performance of Sharia Bank Profit Sharing in Indonesia and to analyze the influence of Bank Assets on the Performance of Sharia Bank Profit Sharing in Indonesia. The population in this study is the Sharia Commercial Bank and Sharia BPR companies that have been registered with Bank Indonesia until the end of 2014 until 2017. The sampling technique uses purposive sampling technique. The analytical tool used in this study is using multiple linear regression. Based on the results of the hypothesis test shows that Good Corporate Governance has a significant influence on the Performance of Profit Sharing; Investment Account Holders has a significant influence on the Performance of Revenue Sharing; There is no influence of Bank Capital on the Performance of Financing for Profit Sharing and Bank Assets that have a significant influence on the Performance of Profit Sharing.